A case study on book censorship against book selection standards and library practices of sectarian high school libraries in District IV of Quezon City - Haduca, Fairlyn R. (2005)
The primary motivation of this study is based on the issue of book censorship against book selection standards and library practices in the library. Censorship is a complex issue that brought up heated discussions and intense studies. The basic problem with censorship is its extremely close relationship with book selection and library practices. Some believe that book selection may result to book censorship while others believe that both book selection and censorship differ with one another.